COMPREHENSIVE EVALUATION OF COMBINED PHARMACOTHERAPY OF CARDIAC PATHOLOGY CONSIDERING EXOGENOUS AND PHARMACOGENETIC FACTORS - Arsen Kornilov; Julia Luneva; Sergej Povetkin (Belgorod National Research University, 2016)
The study assessed changes in hemodynamic and biochemical parameters, vascular age and 5-year cardiovascular risk on the background of complex pharmacotherapy in patients with stable angina I-III functional class (FC), hypertension of I-III degree, chronic heart failure (CHF) II-III FC taking into account the influence of exogenous and pharmacogenetic factors. The study included 200 patients aged 45 - 65 years with concomitant cardiovascular diseases: hypertension of I-III degree, stable angina (I-III FC), with CHF (II-III FC). Patients of the 1st group (100 patients) received prestans, carvedilol, hydrochlorothiazide, verospiron, preparations of acetylsalicylic acid, atorvastatin. Patients of the 2nd group (100 patients) received monopril (fosinopril sodium), carvedilol, amlodipine, hydrochlorothiazide, verospiron, preparations of acetylsalicylic acid, atorvastatin. In hypertensiology part of the study to the end of the observation period the positive dynamics of the main hemodynamic parameters found in both groups. The main indicators of lipid spectrum were improved. Assessment of the impact of pharmacogenetic factors on the effectiveness of the therapy showed no influence of ACE gene polymorphisms (rs4344) and CYP2D6 gene (rs1135840) for the basic hemodynamic parameters, whereas carriers of the genotype (G;G) of the gene CETP (rs4783961) in both groups was associated with a less significant increase of cholesterol of high density lipoproteins (HDL cholesterol) compared with carriers of the allele (A;A) and (A;G). The significant improvement noted in the analysis of the data of vascular age as an integral indicator of the state of the cardiovascular system, as well as a 5-year cardiovascular risk on the background of the combined pharmacotherapy. However, there were not detected statistically significant differences between 1-St and 2-nd groups